1972
DOI: 10.1152/ajplegacy.1972.222.4.864
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to low temperature in hibernating rodents

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The length of the hibernation cycle of hamster is 80-100 h. Torpor lasts for approximately 70 h during which time the whole body MR of the hamster is approximately 2.5% of cenothermic cold adapted RMR [2,3,26]. In torpor, small changes in MR can be performed to defend the reduced body temperature against fluctuations in the low ambient temperature [29,30]. Arousal from hibernation (rectal and brain temperature 4-5°C) to CEN (35-37°C) takes 3-3.5 h at an ambient temperature of 4°C and, on the basis of physiological parameters it can be divided into early, middle and late arousal phases.…”
Section: Animals and Housingmentioning
confidence: 99%
“…The length of the hibernation cycle of hamster is 80-100 h. Torpor lasts for approximately 70 h during which time the whole body MR of the hamster is approximately 2.5% of cenothermic cold adapted RMR [2,3,26]. In torpor, small changes in MR can be performed to defend the reduced body temperature against fluctuations in the low ambient temperature [29,30]. Arousal from hibernation (rectal and brain temperature 4-5°C) to CEN (35-37°C) takes 3-3.5 h at an ambient temperature of 4°C and, on the basis of physiological parameters it can be divided into early, middle and late arousal phases.…”
Section: Animals and Housingmentioning
confidence: 99%
“…It seems clear that thermoreceptivity of CNS persists during hibernation. Hibernating animals increased oxygen consumption and maintained body temperature without arousal in response to cold stimulation (Lyman and O'Brien, 1972;Mills and South, 1972;Hammel et al, 1973;Heller and Colliver, 1974;Weidler et al, 1974). Whether NST contributes to temperature control during the maintenance stage of hibernation is unknown.…”
Section: Cns Control Of Nst During Hibernationmentioning
confidence: 99%
“…However, cortical silence associated with lowered body temperature does not pose a threat to the survival of the animal because important thermoregulatory centers are subcortical. Lyman and O'Brien (11) concluded that peripheral temperature receptors in C. tridecemlineatus and C. lateralis are not involved in temperature regulation during hibernation, and that accurate sensing of decrlines in brain temperature allows the hibernator to arouse from lethal cold.…”
Section: Days Inmentioning
confidence: 99%